How “green” are the green buildings: roles of the government / Gusti Ayu Asri Pramesti ... [et al.] - Asri Pramesti, Gusti Ayu; Andrew, Richard; Gunawan, Juniati; Lee Cg, John (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
This study aimed to explore whether green building disclosures based on the Green Building Council Indonesia (GBCI) have been comprehensively disclosed to stakeholders. The sample was collected from 2020 to 2022, with a total research sample of 94 observations. This study used content analysis in green building disclosure. Data was obtained through annual reports, sustainability, and company websites. The results of the content analysis showed that the disclosure of green building on the website was most on the website (100%) compared to the annual report (73%) and sustainability report (17%). Companies that obtained platinum certification were proven to make higher disclosures than gold and silver. These findings can be used by the Ministry of Public Works and Housing to actively evaluate, control, and direct building owners, contractors, architects, and the public to understand the importance of green building in protecting the environment. In addition, these findings can be used as an evaluation by companies not only in Indonesia but other countries to report green building disclosures to attract investors and provide information on environmental, social, and governance (ESG) performance.